2018
DOI: 10.3184/175815618x15203333340470
|View full text |Cite
|
Sign up to set email alerts
|

Testis Size and Asymmetry in the Guinea Fowl (Numida Meleagris): A Test of the Compensation Hypothesis

Abstract: Despite numerous studies on testicular asymmetry in birds, there are still inconsistent reports on the pattern of asymmetry in species belonging to various phylogenetic groups and exhibiting diverse lifestyles. In addition, there is a lack of clarity on whether functional differences exist between the left and right testes despite differences in size, as well as no evidence of naturally occurring compensation in testis size in terrestrial and galliform birds. A study involving 400 Guinea Fowl (Numida meleagris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…According to previous reports, the right testis is about 10% smaller than the left side ( Sun et al, 2019 ). The testicular asymmetry phenomenon ( Abdul-Rahman et al, 2018 ) was also observed in our study. Similar to our findings, Talebi et al (2018) reported that roosters with higher testes weight were better at sperm quality compared to other roosters.…”
Section: Discussionsupporting
confidence: 86%
“…According to previous reports, the right testis is about 10% smaller than the left side ( Sun et al, 2019 ). The testicular asymmetry phenomenon ( Abdul-Rahman et al, 2018 ) was also observed in our study. Similar to our findings, Talebi et al (2018) reported that roosters with higher testes weight were better at sperm quality compared to other roosters.…”
Section: Discussionsupporting
confidence: 86%
“…In many species, older males have larger testes because they have reached sexual maturity, and there is also some evidence for an increase in asymmetry between testes with age (Merila and Sheldon 1999, Brown and Brown 2003, Abdul-Rahman et al 2018. Perhaps the pattern of old males having smaller testes reflects a trade-off between reproduction and longevity (Austad and Hoffman 2018); if older males have invested more resources in survival and maintenance than younger males, this investment could come at the expense of reproductive somatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their length, the width of the left and right testes in Cemani chickens has been observed to exceed that of Sentul chickens [11]. On the contrary, an examination of the average weight of the left and right testes in Cemani chickens reveals a lower value compared to the naked neck and curly hair in the Southern Guinea Savanna region of Nigeria [30]. However, a higher value compared to Sentul chickens [11].…”
Section: Testes Morphometricmentioning
confidence: 93%
“…However, a higher value compared to Sentul chickens [11]. A change in our attention is directed towards another type of bird, as an investigation has unveiled that in the Guinea Fowl, the left testes show a magnitude that is roughly 10% larger than that of the right testes [30]. Testicular augmentation is regulated using photoperiod, nutrition, and gene expression, which subsequently modulate the hypothalamic-pituitary axis and initiate gonadal augmentation.…”
Section: Testes Morphometricmentioning
confidence: 99%